2020
DOI: 10.1002/ccd.29425
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and sudden death after chronic total occlusion percutaneous coronary intervention: Prognostic role of the target vessel

Abstract: Background The role of the target vessel in percutaneous revascularization of chronic total occlusion (CTO) is unclear. Objective We sought to assess the long‐term results of percutaneous coronary intervention (PCI) for CTO lesions in each coronary artery and to investigate the impact of successful revascularization and previous myocardial infarction (MI) in the territory of the target vessel. Methods and Results Cohort observational study on 1,124 patients who have undergone CTO PCI attempt: 371 on left anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…34 In addition, malignant arrhythmias may have an important role in the pathophysiology of cardiovascular death in patients with coronary CTOs. 20,[30][31][32]35,36 Moreover, it has been suggested that nonrevascularized CTOs may be associated with impaired LVEF which is a well-established prognostic marker for major adverse cardiovascular events. 16 However, in the case of patients undergoing TAVR the risk is different from that of acute myocardial infarction.…”
Section: Study Id Coronary Artery Disease Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In addition, malignant arrhythmias may have an important role in the pathophysiology of cardiovascular death in patients with coronary CTOs. 20,[30][31][32]35,36 Moreover, it has been suggested that nonrevascularized CTOs may be associated with impaired LVEF which is a well-established prognostic marker for major adverse cardiovascular events. 16 However, in the case of patients undergoing TAVR the risk is different from that of acute myocardial infarction.…”
Section: Study Id Coronary Artery Disease Resultsmentioning
confidence: 99%
“…In case of an acute vessel closure in the collateral donor artery mortality increases to an excessive 52% 34 . In addition, malignant arrhythmias may have an important role in the pathophysiology of cardiovascular death in patients with coronary CTOs 20,30–32,35,36 . Moreover, it has been suggested that nonrevascularized CTOs may be associated with impaired LVEF which is a well‐established prognostic marker for major adverse cardiovascular events 16 .…”
Section: Discussionmentioning
confidence: 99%